Cervical clamp with ring forceps to prevent prolapse of an intrauterine balloon in the management of postpartum hemorrhage. Issue 3 (29th October 2012) - Kawamura, Akeo; Kondoh, Eiji; Hamanishi, Junzo; Kawamura, Yosuke; Kusaka, Kyoko; Ueda, Akihiko; Kawasaki, Kaoru; Fujita, Kohei; Mogami, Haruta; Konishi, Ikuo
Abstract: An intrauterine balloon tamponade is a simple but highly effective method for the management of postpartum hemorrhage. However, treatment failure can occur due to prolapse of an intrauterine balloon into the vagina. We present two cases with a successful maneuver in maintaining the intrauterine placement of the balloon by clamping the cervix with two ring forceps in the management of postpartum hemorrhage. Although the balloon was initially expelled through a dilated cervix, a cervical clamp using ring forceps prevented displacement of the balloon, and the hemorrhage ceased. Clamping the cervix with two ring forceps to retain the balloon can be a simple and readily available approach to consider when an intrauterine balloon tamponade does not work due to its expulsion.